Toward a Self-Reflexive Law? Narrating Torture’s Legality in Human Rights Litigation - Natalie R. Davidson (Law Text Culture, 2017)
This essay’s starting point is scholarship describing the state practice of using law as a tool of mass atrocity, and the part played by liberal trials in obscuring this ‘dark side’ of legality. It asks whether law’s complicity with atrocity is only visible when one steps outside the legal arena, or whether there might be opportunities within liberal legal institutions to develop what the essay calls self-reflexive law: rule of law mechanisms that expose the part played by law in violence. To explore this question, the essay offers a close reading of a lawsuit in which the key part played by law in atrocity was made explicit at trial: a class action filed in 1986 under the Alien Tort Statute on behalf of 10,000 Philippine victims of torture and other gross abuses against Ferdinand Marcos. Studying the representations of violence produced by the various participants in the litigation, the essay attempts to elicit some of the legal and political conditions favorable to a self-reflexive law. The essay offers a distinct version of ‘minor jurisprudence,’ recovering ‘minor’ practices within orthodox law itself, namely oral trial proceedings, and attempting to derive insights from the minor in order to contribute to legal design.